Pengaruh Tunjangan Kinerja, Sertifikasi Guru dan Motivasi terhadap Kinerja Guru pada Sekolah MIN dalam Gugus Peusangan Kabupaten Bireuen - Salma, Salma; Yusuf, M. (Aceh Cooperative Care, 2023)
Teacher performance factors in Ministry of Religion schools such as Madrasah Ibtidaiyah Negeri (MIN) are still being discussed, so evaluation studies and research into the causal factors are still being carried out. This research also tries to look at the provision of performance allowances, teacher certification factors and teacher motivation. Research on 99 MIN teachers in the Peusangan Cluster, Bireuen Regency. The research method used is associative with a quantitative approach. And problem analysis uses statistics through path analysis. The results of data analysis prove: (a) there is a direct and indirect influence of performance allowances on teacher performance of 47.61%, (b) teacher certification factors have a direct and indirect influence on teacher performance of 44.34%, and also (c) there is a direct and indirect influence of work motivation on teacher performance of 33.69%. Simultaneously, these three factors made a positive contribution to efforts to increase performance by 66.7%.